BERSAMA KITA BANGKIT MELAWAN COVID-19 - Rahayu, Supriati Hardi; Syaifudin, Ahmad; Nugrahaeni, Mentari Nur; Khoirunnisa, Nur Ifani (Gemi: Jurnal Penelitian dan Pengabdian, 2022)
One of the problems that exist in the people of Kedon Hamlet, Congkrang Village, Muntilan District, Central Java Province is the lack of awareness of the potential around them that they might be able to use as additional resources to be useful for the community. One of the programs implemented in Kedon Hamlet is Tutoring. The aims of the Tutoring Program are: 1) To create public awareness of the importance of science; 2) To realize quality, character, creative and innovative Human Resources; 3) To encourage and motivate children to be enthusiastic in learning and achieving achievements. The result of this Tutoring program is that the children are enthusiastic in participating in these activities. In addition, this Tutoring program can also help students who have difficulty in working on the practice questions given during learning activities at school.